Sadum: Traditional and Contemporary - Ratna Panggabean (Journal of Visual Art and Design, 2009)
Sadum is one of the traditional cloths of the Batak people in North Sumatra. It is woven on a back strap loom with supplementary weft technique. Sadum is a warp faced weaving made of cotton and beads woven into the cloth. Ritually it is used as a shoulder cloth, gifts exchanges, and in dances. It also bears the symbol of good tidings and blessings for the receiver. The cloth has change during times in technique, color, patterns, as well as in functions. But the use as a ritual cloth stays the same. The basic weaving techniques and equipments used to create it hasn't change, but its material and added techniques has made this cloth become more rich in color, pattern, and texture. Most changes began when the Europeans came to Indonesia and introduced new material such as synthetic fibers and colors. In the 70s traditional cloth of Indonesia got its boost when the government declared batik as Indonesian national attire. This encourages other traditional weavings to develop into contemporary clothing. Later, new techniques and material were introduced to the Sadum weavings including embroidery, silk and golden threads which were never used before.